Enterprise Innovation Commercialization Methods - Anna S. OBUKHOVA; Nataliya A. MASHKINA; Olga V. BELYAEVA; Elena S. BELYAEVA; Tatiyana N. POLYAKOVA (Communications of International Proceedings, 2021)
The article discusses the commercialization of innovations as an integral part of innovation. Commercialization is understood as a set of actions of an innovation developer to bring an innovative product to the market, from identifying prospects for its commercial use to implementation and obtaining an economic effect. Participants in the commercialization process directly play a significant role in this process. The process of commercializing innovations includes several stages. At the first stage, there is a search for new ideas, technologies and processes. The search is carried out both within the enterprise, if the enterprise has previously unclaimed innovations, and in the external environment - from competitors, suppliers, consumers. The second stage of the commercialization process is the formation of the necessary financial resources. The main task for an enterprise at this stage is to attract an investor - in the form of a bank, another enterprise or a state, since only a few enterprises have sufficient funds for self-financing of development. At the third stage, the rights to the created innovation are legally secured with their distribution among all participants in the process. The fourth stage of commercialization involves the introduction of innovations into production either in the form of organizing the production of an innovative product with its further support and refinement, if necessary, or in the form of using this innovation in the production process to improve the efficiency and quality of products.
Keywords: Innovation; Innovation; Commercialization of Innovation; Product Innovation; Technology Transfer Methods.